Urgensi kompetensi guru bimbingan dan konseling di sekolah dan prestasi belajar siswa - Rezky Permatasari (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2017)
Learning achievement is a baseline of success in education. In an effort to educate students, then the competence of school counselors is an important thing to have. Competent school counselors will be able to make students motivated in learning. These competencies include pedagogical, personality, social and professional competence. This also applies not only to subject teachers but also to school counselors. School counselors who have high competence have a great influence on the achievement of student learning, because with guidance and counseling services are optimal, a student is able to encourage himself to achieve learning achievement.